2007
DOI: 10.1136/jech.2006.043133
|View full text |Cite
|
Sign up to set email alerts
|

Eye discomfort, headache and back pain among Mayan Guatemalan women taking part in a randomised stove intervention trial

Abstract: Background: Indoor air pollution (IAP) from combustion of biomass fuels represents a global health problem, estimated to cause 1.6 million premature deaths annually. Aims: RESPIRE (Randomised Exposure Study of Pollution Indoors and Respiratory Effects) Guatemala is the first randomised controlled trial ever performed on health effects from solid fuel use. Its goal is to assess the effect of improved stoves (planchas) on exposure and health outcomes in a rural population reliant on wood fuel. Methods: Questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 11 publications
8
71
0
1
Order By: Relevance
“…In China specifically, it has been determined that broad health risk education methods are insufficient to reduce indoor air pollution exposures from cooking and heating and that resources should be used to propagate infrastructure changes to reduce the exposures (Jin et al, 2006); stove improvements are, therefore, crucial for reducing the negative health effects associated with in-home fuel combustion. Stove improvements have been shown to reduce the short-term negative health effects associated with fuel combustion exposures, such as acute respiratory infections in children in India (Akunne et al, 2006) and eye irritation and headaches in women in Guatemala (Diaz et al, 2007), by reducing indoor air pollution (Naeher et al, 2000). Previous analyses of the Xuanwei cohort strongly suggest that CIs ¼ confidence intervals; HRs ¼ hazard ratios.…”
Section: Discussionmentioning
confidence: 99%
“…In China specifically, it has been determined that broad health risk education methods are insufficient to reduce indoor air pollution exposures from cooking and heating and that resources should be used to propagate infrastructure changes to reduce the exposures (Jin et al, 2006); stove improvements are, therefore, crucial for reducing the negative health effects associated with in-home fuel combustion. Stove improvements have been shown to reduce the short-term negative health effects associated with fuel combustion exposures, such as acute respiratory infections in children in India (Akunne et al, 2006) and eye irritation and headaches in women in Guatemala (Diaz et al, 2007), by reducing indoor air pollution (Naeher et al, 2000). Previous analyses of the Xuanwei cohort strongly suggest that CIs ¼ confidence intervals; HRs ¼ hazard ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Following Diaz et al (2007), we measured Carbon Monoxide (CO) in exhaled breath to measure smoke inhalation. As discussed in the data section, CO is a biomarker of recent exposure to air pollution from biomass combustion, and therefore it can be used to proxy an individual's personal exposure to smoke from cooking stoves.…”
Section: B Effects On Smoke Inhalationmentioning
confidence: 99%
“…Notably, Guatemalan women reported fewer headache and less eye discomfort after installation of improved wood burning stoves [31] while the use of cleaner household fuels coincided with a 31% decrease in childhood mortality in subSaharan Africa [32]. In this study, we documented improvements in self-reported respiratory health of women and children, and the respiratory health of women as determined by spirometry readings, after adoption of more efficient stoves.…”
Section: Respiratory Healthmentioning
confidence: 62%